Parental Caring, Pengetahuan Menstruasi, dan Tingkat Kecemasan Menghadapi Menarche pada Siswi Sekolah Dasar: Parental Caring, Menstrual Knowledge, and Anxiety Levels Facing Menarche Among Elementary School Students - Komsiyah; Dian Nur Kumalasari; Fhandy Aldy Mandaty; Achmad Syaifudin; Ayu Dita Handaningtyas; Sumarno (Jurnal Keperawatan Berbudaya Sehat, 2026)
Menarche (the first menstruation) is a physiological change that frequently triggers anxiety in adolescent girls due to a lack of knowledge and informational preparedness. This study aims to determine the relationship between parental caring and knowledge levels with anxiety levels among elementary school students facing menarche. This quantitative study utilized a cross-sectional design. Total sampling was employed, involving 59 elementary school students at SD Sekaran 02 Semarang as respondents in December 2025. Data were analyzed using the Chi-Square statistical test. The univariate results showed that the majority of respondents had a moderate perception of parental caring (57.6%), a moderate level of knowledge (59.3%), and a mild anxiety level (50.8%). The bivariate Chi-Square test results for the parental caring variable showed a p-value of 0.523 > α (0.05). Meanwhile, the Chi-Square test for the knowledge level variable showed a p-value of 0.018 < α (0.05). In conclusion, there is no significant relationship between the perception of parental caring and students' anxiety levels in facing menarche. Conversely, a significant relationship exists between the level of knowledge and the anxiety levels of elementary school students facing menarche. Early reproductive health education needs to be enhanced to optimize students' psychological preparedness.